Advances and challenges in drug design against dental caries: Application of in silico approaches - Chen, Zhongxin; Zhao, Xinyao; Zheng, Hanyu; Wang, Yufei; Zhang, Linglin (Journal of pharmaceutical analysis, 2025)
Dental caries, a chronic disease characterized by tooth decay, occupies the second position in terms of disease burden and is primarily caused by cariogenic bacteria, especially Streptococcus mutans, because of its acidogenic, aciduric, and biofilm-forming capabilities. Developing novel targeted anti-virulence agents is always a focal point in caries control to overcome the limitations of conventional anti-virulence agents. The current study represents an up-to-date review of in silico approaches of drug design against dental caries, which have emerged more and more powerful complementary to biochemical attempts. Firstly, we categorize the in silico approaches into computer-aided drug design (CADD) and AI-assisted drug design (AIDD) and highlight the specific methods and models they contain respectively. Subsequently, we detail the design of anti-virulence drugs targeting single or multiple cariogenic virulence targets of S. mutans, such as glucosyltransferases (Gtfs), antigen I/II (AgI/II), sortase A (SrtA), the VicRK signal transduction system and superoxide dismutases (SODs). Finally, we outline the current opportunities and challenges encountered in this field to aid future endeavors and applications of CADD and AIDD in anti-virulence drug design. [Display omitted] •Specific methods and models with CADD and AIDD are comprehensively summarized.•The design of single- and multi-target drugs against Streptococcus mutans are detailed.•The current limitations of targeted anti-caries drug design were discussed.